Efektivitas Program Mindfulness Dalam Menurunkan Burnout Pada Perawat: Systematic Literature Review - Puji Mukti Hartani; Dulides Kristianto Welly; Dwi Natalia Rustanti; Dahlia Dahlia; Lindawati BR Barus; Bambang Sumantri; Suriadi Suriadi; Supriadi Supriadi; Imran Imran (Universitas Pahlawan Tuanku Tambusai, 2026)
Burnout is a serious psychological condition widely experienced by nursing professionals due to the persistently high demands of clinical work environments. This condition is characterized by prolonged emotional exhaustion, depersonalization toward patients, and a diminished sense of personal accomplishment, all of which directly compromise the quality of healthcare delivery. This study aims to analyze and synthesize scientific evidence regarding the effectiveness of mindfulness programs in reducing burnout among nurses through a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. A total of 10 articles published between 2022 and 2025 were included following a rigorous selection process from 309 initially retrieved records across multiple electronic databases. The synthesis reveals that mindfulness programs, particularly Mindfulness-Based Stress Reduction (MBSR), consistently and significantly reduce emotional exhaustion and depersonalization while enhancing nurses' sense of personal accomplishment. Optimal effectiveness is achieved through structured programs lasting 8 to 12 weeks, supported by adequate institutional commitment and high participant adherence. Digital-based mindfulness interventions also demonstrated broader accessibility and promising outcomes across diverse clinical settings. These findings strongly recommend the formal integration of mindfulness programs into continuing professional development systems for nursing staff within healthcare institutions.